Investigation of the effects of indoxyl sulfate, a uremic toxin, on the intracellular oxidation level and phagocytic activity using an HL-60-differentiated human macrophage cell model. Issue 5 (3rd May 2020) - Tsutsumi, Shuhei; Tokunaga, Yuki; Shimizu, Shunsuke; Kinoshita, Hideki; Ono, Masateru; Kurogi, Katsuhisa; Sakakibara, Yoichi; Suiko, Masahito; Liu, Ming-Cheh; Yasuda, Shin
ABSTRACT: Indoxyl sulfate (IS), a uremic toxin, is a sulfate-conjugated metabolite originated from tryptophan. Accumulating uremic toxins may worsen renal diseases and further complicate related disorders including impaired immune functions under oxidative stress conditions. However, it has remained unclear whether or not IS can directly cause the cellular immune dysfunction. We investigated the effects of IS on the intracellular oxidation level and phagocytic activity in a HL-60-differantiated human macrophage cell model. Incubation of the cells in the presence of IS resulted in increasing intracellular oxidation level and decreasing phagocytic activity. In addition to inhibitors for NADH oxidase (NOX), organic anion transporting polypeptide2B1 (OATP2B1), protein kinase C (PKC), and phosphoinositide 3-kinase (PI3K), a representative antioxidant Trolox, was also shown to significantly relieve the IS-induced oxidation and restore weakened phagocytosis. Collectively, IS may directly down-regulate the phagocytic immune function of macrophages through the oxidation mechanisms including OATP2B1, PKC, PI3K, and NOX pathways. Abbreviations: CKD: Chronic kidney disease; IS: Indoxyl sulfate; ROS: Reactive oxygen species; NOX: NADH oxidase; OATP2B1: Organic anion transporting polypeptide2B1; PKC: Protein kinase C; PI3K: Phosphoinositide 3-kinase; 2-APT: 2-acetylphenothiazine Graphical abstract: uf0001 Effects of indoxyl sulfate, a uremic toxin, on the intracellular oxidation level and phagocytic activity using a human macrophage cell model.